FINANCIAL FREEDOM AND BANK EFFICIENCY: THE ROLE OF NATIONAL GOVERNANCE QUALITY - Đoàn Anh Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
This paper investigates the impacts of fianancial freedom and national governance quality on bank efficiency, employing data of 37 Vietnam commercial banks over the period 2003 – 2014. Using stochatic frontier approach to estimate bank efficiency scores, the author finds the evidence that increase in financial freedom is positively associated with bank efficiency. The results also show that most indicators of Vietnam governnance quality tend to play an important role in improving the relation between financial freedom and bank efficiency.